Co2SnO4 nanocrystals anchored on graphene sheets as high-performance electrodes for lithium-ion batteries. (1st January 2015) - Chen, Chang; Ru, Qiang; Hu, Shejun; An, Bonan; Song, Xiong; Hou, Xianhua
Highlights: Cubic spinel Co2 SnO4 /G nanocomposites are synthesized by a facile hydrothermal process. Co2 SnO4 /G nanocomposites show more excellent electrochemical performance than pure Co2 SnO4 nanoparticles. The nanocomposites demonstrate a high reversible discharge capacity of 1061.1 mAh g −1 at 100 mA g −1 after 100 cycles. Abstract: Cubic spinel Co2 SnO4 /graphene sheets (Co2 SnO4 /G) nanocomposites are synthesized by a facile hydrothermal process in alkaline solution, using SnCl4  · 4H2 O, CoCl2  · 6H2 O and graphene oxide (GO) as the precursor. The structure and morphology of the resulting nanocomposites are characterized with X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Co2 SnO4 nanoparticles are uniformly dispersed among graphene sheets, with a size of 80–150 nm. As anode material for lithium-ion batteries, the galvanostatic charge/discharge and cyclic voltammetry are conducted to indicate the electrochemical performance of Co2 SnO4 /G nanocomposites. Co2 SnO4 /G nanocomposites exhibit an improved electrochemical performance compared with pure Co2 SnO4 nanoparticles, such as high reversible capacities, good cycling stability and excellent rate performance. The initial charge and discharge capacities are 996.1 mAh g −1 and 1424.8 mAh g −1 . After 100 cycles, the reversible charge/discharge capacities still remain 1046/1061.1 mAh g −1 at the current density of 100 mA g −1 . Co2 SnO4 nanoparticles coated by Graphene sheets with superior electrochemical performance indicate that Co2 SnO4 /G nanocomposites are promising electrode materials used for high-storage lithium-ion batteries.